Latent Profile Analysis of Cumulative Stress and Protective Factors in Junior High School Students' Problematic Internet Use. - Zheng, Xintong; Xue, Chao; Chen, Jianwen (International Journal of Mental Health & Addiction, 2026)
Problematic Internet use (PIU) is a significant mental health concern. Previous research has focused on the risk and protective factors associated with PIU but has overlooked the specific categories of stress and protective factors that individuals encounter in real-life situations from a person-centered approach. The sample consisted of 2186 Chinese junior high school students who completed questionnaires assessing cumulative stress and protective factors regarding PIU. Using latent profile analysis (LPA), a person-centered statistical approach, a three-profile model of cumulative stress for PIU was suggested as the optimum: high punishment-peer victimization, high punishment-negative social relationships, and high academic pressure-health adaptation stress. As for protective factors against PIU, a three-profile solution (low levels of protective factors-high humor, low levels of protective factors-high emotional intelligence, and high levels of protective factors-low emotional intelligence) was also the most appropriate one in our study. Finally, analysis of variance (ANOVA) was employed to examine disparities in PIU across different profiles. These findings emphasized the differences in profiles of cumulative stress and protective factors on PIU scores, suggesting that intervention practitioners should provide targeted interventions for these distinct groups.